Enzymatic synthesis of 6-O-glucosyl-poly(3-hydroxyalkanoate) in organic solvents and their binary mixture - Gumel, A.M.; Annuar, M.S.M.; Heidelberg, T. (Elsevier, 2013)
The effects of organic solvents and their binary mixture in the glucose functionalization of bacterial poly- 3-hydroxyalkanoates catalyzed by LecitaseTM Ultra were studied. Equal volume binary mixture of DMSO and chloroform with moderate polarity was more effective for the enzyme catalyzed synthesis of the carbohydrate polymer at≈38.2 (±0.8)% reactant conversion as compared to the mono-phasic and other binary solvents studied. The apparent reaction rate constant as a function of medium water activity (aw)was observed to increase with increasing solvent polarity, with optimum aw of 0.2, 0.4 and 0.7 (±0.1) observed in hydrophilic DMSO, binary mixture DMSO:isooctane and hydrophobic isooctane, respectively.Molecular sieve loading between 13 to 15 g L−1 (±0.2) and reaction temperature between 40 to 50 ◦C were found optimal. Functionalized PHA polymer showed potential characteristics and biodegradability.